Diet and oral health of populations that inhabited central Argentina (Córdoba Province) during late holocene - Fabra, Mariana (2015)
The aim of this work is to study, from a bioarchaeological perspective, the diet and oral health of the populations that inhabited Central Argentina in two periods which would reflect changes in subsistence strategies: earlier late Holocene (ca. 2500-1500years BP) and later late Holocene (ca.1500-400years BP). The sample is composed by 83 adult individuals from 47 archaeological sites. We considered five non-specific indicators of stress, infectious and degenerative diseases: hypoplasia of dental enamel, dental caries, abscesses, antemortem teeth loss, and calculus. We also considered hypercementosis, dens in dens, and agenesis. We test intraobserver error by means of intraclass correlation coefficient and analysis of variance of repeated measures. We calculated prevalence by sex, age, geographic subregion, and chronological period. We applied Chi-square (X2) to test statistical significance of observed differences. Considering the sample as a whole, low prevalence of dental caries (10.27%), abscesses (16.52%), and hypoplasia (10.84%) are coincident with values observed for populations with mixed or hunter-gathering subsistence strategy. In later late Holocene, high incidence of caries should be considered as indicator of consumption of C4 vegetables or other carbohydrate-rich vegetables, such as legumes of Prosopis sp. Also, moderate values of dental enamel hypoplasia should be related with metabolic-systemic stress episodes. Summarizing, these results are coincident with isotopic, archaeological, and ethnohistorical evidences which suggest climatic, social, and demographic pressures that might have affected the lifestyle of these populations before the Spanish conquest.